Paraguay : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
This Selected Issues paper analyzes the background, stages and developments, and estimation of the direct costs of Paraguay's banking crisis. The paper provides the estimates on the size and evolution of the informal sector, and examines the extent to which the national accounts capture informal activity. The study also estimates the potential output and total factor productivity by examining trends in output, investment, and population growth as well as the direction and size of fiscal impulse on its economy. The paper also provides a statistical appendix report of Paraguay.